VARIASI SUARA DALAM BAHASA GAUL: Pengaruh Media Sosial Terhadap Fonologi Remaja - Cathrin Natalia Simarmata; Maikel Brekana Ginting; Putri Ayu Adelina Situmorang; Windi Aura (Journal Education and Government Wiyata, 2025)
This article examines sound variation in slang, with a focus on the influence of social media on phonology among adolescents. In the digital era, slang has developed rapidly, creating a unique and dynamic form of communication. This research analyzes the phonological changes that occur in the use of slang, including the phenomena of assimilation, obliteration, and sound adjustment that are often found in online interactions. Through collecting data from popular social media platforms, this article explores how voice variations not only reflect adolescents' social and cultural identities, but also contribute to the formation of new linguistic norms. The findings show that slang not only functions as a means of communication, but also as a means of expressing linguistic creativity among the younger generation. By understanding phonological variation in slang, this article aims to provide insight into the dynamics of contemporary language and its important role in the development of modern linguistics.